2009
DOI: 10.1091/mbc.e09-04-0276
|View full text |Cite
|
Sign up to set email alerts
|

IC97 Is a Novel Intermediate Chain of I1 Dynein That Interacts with Tubulin and Regulates Interdoublet Sliding

Abstract: Our goal is to understand the assembly and regulation of flagellar dyneins, particularly the Chlamydomonas inner arm dynein called I1 dynein. Here, we focus on the uncharacterized I1-dynein IC IC97. The IC97 gene encodes a novel IC without notable structural domains. IC97 shares homology with the murine lung adenoma susceptibility 1 (Las1) protein--a candidate tumor suppressor gene implicated in lung tumorigenesis. Multiple, independent biochemical assays determined that IC97 interacts with both alpha- and bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 72 publications
1
53
0
Order By: Relevance
“…Our 2DE analysis did not identify additional I1 components, but polypeptides larger than ∼150 kDa are difficult to resolve by this technique. Consistent with previous studies, we identified only a single isoform of IC97 (20,34) (Fig. 6 and Fig.…”
Section: I1 Intermediate Chain Assembly Into the Axoneme Of Wt And I1supporting
confidence: 92%
See 1 more Smart Citation
“…Our 2DE analysis did not identify additional I1 components, but polypeptides larger than ∼150 kDa are difficult to resolve by this technique. Consistent with previous studies, we identified only a single isoform of IC97 (20,34) (Fig. 6 and Fig.…”
Section: I1 Intermediate Chain Assembly Into the Axoneme Of Wt And I1supporting
confidence: 92%
“…1). A number of I1 components have been identified biochemically, including three intermediate chains (IC140, IC138, and IC97), several light chains (LC8, LC7a, LC7b, Tctex1, and Tctex2b), and the accessory protein FAP120 (11,13,16,(23)(24)(25)(28)(29)(30)(31)(32)(33)(34). A recent study of an IC138 null mutant (bop5-2) revealed that IC138 is required for assembly of an "IC138 subcomplex" consisting of IC138, IC97, LC7b, and FAP120 (21).…”
mentioning
confidence: 99%
“…As noted above, null mutants and RNAi knockdowns are valuable but provide limited information about molecular mechanisms. Recent elegant studies on inner-arm and outer-arm dynein subunits in Chlamydomonas have made important steps toward addressing this issue (16,32,41,44), but investigating specific functions and molecular mechanisms of flagellum proteins remains a major challenge. The inducible system that we have developed in T. brucei offers an opportunity for systematic mutational analysis of virtually any flagellar protein in a background where the endogenous protein is reduced or absent.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the light intermediate chain (DLIC) of the retrograde IFT motor CD1b (25,27), IC140 in I1 (28), p28 in single-headed IDAs (29), and IC78, LC6, and LC9 of the ODA (30) were not obviously affected. Interestingly, IC97 (also called IC110) in I1 (31) was not detectable, indicating IC97 is the missing 110-kDa IDA component in pf5 (20) and is not essential for the assembly of I1.…”
Section: Pf5 Mutant Displays Multiple Flagellar Defects Because Of Amentioning
confidence: 99%
“…The actual target proteins of LC8 in I1 have not been determined. However, neither IC138, a candidate scaffold molecule with WD repeats, nor IC97, which is most sensitive to the LC8 mutations, is required for I1 assembly (31,35). Instead, both are implicated in phosphoregulation of I1 (31,35,36).…”
Section: Lc8 Promotes the Formation Of The Retrograde Ift Motor For Tmentioning
confidence: 99%